Understanding UN Discourse: A Multifaceted Analysis ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with the intricacies of UN discourse, examining its role in global diplomacy. We explore how the United Nations, a linchpin of international relations, utilizes various forms of discourse to shape perceptions, navigate power dynamics, and promote human rights. By analyzing UN context, key actors, and power structures, we reveal the nuanced interplay of language, rhetoric, and diplomacy within the UN. This article highlights the influence of powerful nations, the use of veto power, and the soft power of discourse in shaping international outcomes. Human rights, a central UN focus, are scrutinized for their dependence on effective discourse. Through case studies, including the Universal Declaration of Human Rights and climate change agreements, we dissect the language and strategies that drive UN initiatives. Looking ahead, we consider the future of UN discourse in an evolving global landscape, emphasizing its enduring importance in international relations.